Simulation of polar ozone depletion: An update - Solomon, Susan; Kinnison, Doug; Bandoro, Justin; Garcia, Rolando (Journal of Geophysical Research: Atmospheres, 2015)
We evaluate polar ozone depletion chemistry using the specified dynamics version of the Whole Atmosphere Community Climate Model for the year 2011. We find that total ozone depletion in both hemispheres is dependent on cold temperatures (below 192 K) and associated heterogeneous chemistry on polar stratospheric cloud particles. Reactions limited to warmer temperatures above 192 K, or on binary liquid aerosols, yield little modeled polar ozone depletion in either hemisphere. An imposed factor of three enhancement in stratospheric sulfate increases ozone loss by up to 20 Dobson unit (DU) in the Antarctic and 15 DU in the Arctic in this model. Such enhanced sulfate loads are similar to those observed following recent relatively small volcanic eruptions since 2005 and imply impacts on the search for polar ozone recovery. Ozone losses are strongly sensitive to temperature, with a test case cooler by 2 K producing as much as 30 DU additional ozone loss in the Antarctic and 40 DU in the Arctic. A new finding of this paper is the use of the temporal behavior and variability of ClONO[subscript 2] and HCl as indicators of the efficacy of heterogeneous chemistry. Transport of ClONO[subscript 2] from the southern subpolar regions near 55–65°S to higher latitudes near 65–75°S provides a flux of NO[subscript x] from more sunlit latitudes to the edge of the vortex and is important for ozone loss in this model. Comparisons between modeled and observed total column and profile ozone perturbations, ClONO[subscript 2] abundances, and the rate of change of HCl bolster confidence in these conclusions. National Science Foundation (U.S.) (NSF FESD grant OCE-1338814) National Science Foundation (U.S.) (grant, NSF Atmospheric Chemistry Division)